2022
DOI: 10.37275/bsm.v6i5.515
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Interleukin-6 Levels with Clinical Features and Chest X-Ray Imaging in Coronavirus Disease-19 (COVID-19) Patients at Dr. Mohammad Hoesin General Hospital Palembang

Abstract: Background. COVID-19 infection, both moderate and severe symptoms can cause pneumonia that can be detected on a chest X-ray. Along with the increasing severity of the clinical picture of COVID 19, it can also trigger a cytokine storm, one of which is an increase in Interleukin-6 levels. This study was conducted to see the correlation between IL-6 levels with clinical features and chest radiographs in patients with COVID-19 Methods. This research is a cross-sectional study using an observational analytic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…13,20 Study in Palembang, Indonesia, showed a correlation between IL-6 levels in COVID-19 with chest X-rays and clinical features. 21 A study by Guirao et al 22 also showed that IL-6 could better predict COVID-19 disease severity. IL-6 level correlates with other clinical parameters to evaluate the severity of COVID-19.…”
Section: Discussionmentioning
confidence: 98%
“…13,20 Study in Palembang, Indonesia, showed a correlation between IL-6 levels in COVID-19 with chest X-rays and clinical features. 21 A study by Guirao et al 22 also showed that IL-6 could better predict COVID-19 disease severity. IL-6 level correlates with other clinical parameters to evaluate the severity of COVID-19.…”
Section: Discussionmentioning
confidence: 98%